18F-FDG PET/CT for Monitoring the Response of Breast Cancer to miR-143-Based Therapeutics by Targeting Tumor Glycolysis - Ying Miao; Ling-fei Zhang; Rui Guo; Sheng Liang; Min Zhang; Shuo Shi; Cheng-fang Shang-Guan; Mo-fang Liu; Biao Li (Molecular Therapy: Nucleic Acids, 2016)
Increased glucose utilization is a hallmark of cancer, and tumor metabolism is emerging as anticancer target for therapeutic intervention. Triple-negative breast cancers TNBC are highly glycolytic and show poor clinical outcomes. We previously identified hexokinase 2, the major glycolytic enzyme, as a target gene of miR-143 in TNBC. Here, we developed a therapeutic formulation using cholesterol-modified miR-143 agomir encapsulated in a neutral lipid-based delivery agent that blocked tumor growth and glucose metabolism in TNBC tumor-bearing mice when administered systemically. The antioncogenic effects were accompanied by a reduction in the direct target hexokinase 2 and [18F]-fluorodeoxyglucose (18F-FDG) uptake based on positron emission tomography/computed tomography. Treatment with miR-143 formulation has minimal toxic effects and mice tolerated it well. Thus, we demonstrated that miR-143 is a robust inhibitor of the Warburg effect and an effective therapeutic target for TNBC. In addition, 18F-FDG positron emission tomography/computed tomography can be used to specifically monitor the response of TNBC to miR-143-based therapeutics by targeting tumor glycolysis.